Analysis of Different Boundary Conditions on Homogeneous One-Dimensional Heat Equation - Norazlina Subani; Muhammad Aniq Qayyum Mohamad Sukry; Muhammad Arif Hannan; Faizzuddin Jamaluddin; Ahmad Danial Hidayatullah Badrolhisam (USIM Press, 2024)
MJoSHT2021, Volume 7, Issue 1, eISSN: 2601-0003